Unicornileptura gen. nov., a unique lepturine genus from China (Coleoptera, Cerambycidae, Lepturinae, Lepturini) - Bi, Wen-Xuan; Chen, Chang-Chin; Ohbayashi, Nobuo (Zootaxa, 2022)
Unicornileptura gen. nov. (独角花天牛属, Dú jiǎo huā tiān niú shǔ) is established for Unicornileptura emeiensis sp. nov. from Sichuan (as the type species) and U. laticollis sp. nov. from Hubei. Illustrations of habitus, endophallic structure and major diagnostic features are provided.